Development of a Website-Based Halal Supply Chain Management Information System Model and its Implications for Productive Zakat Management - Surya Pratikto, Muhammad Iqbal; Arifin, Ah. Ali; Azizah Malik, Rizki (Management of Zakat and Waqf Journal (MAZAWA), 2024)
a food can be said to be halal or haram not only seen from the basic ingredients, but broader than that, it needs to be seen from additional ingredients, processing, production processes, packaging, distribution, storage to the final consumer ‘end-user’. Therefore, the supply chain is an approach that is in accordance with the indicators of food that can be said to be halal. This research aims to describe the concept of Halal Supply Chain for chicken and beef commodities whose management model can have implications for the management of productive zakat funds. In addition, designing a website-based technology system for halal beef and chicken supply chains The research approach used in this research is a qualitative approach using data collection methods of interviews, observation, and documentation, after the data is collected, the data is processed using the system development life cycle (SDLC) method. The system development life cycle (SDLC) consists of 6 stages, namely planning (planning), analysis (analysis), design (design), development (development), testing or implementation (testing & integration), and the last is maintenance (maintenance). The results obtained from this study define the concept of halal supply chain for chicken and beef commodities as a series of processes from upstream to downstream that apply halal principles in every process. Researchers designed a technological breakthrough in a series of halal supply chain processes packaged in a container called a website/application. The use of the website is expected to facilitate every process carried out by stake holders or business actors involved in the halal supply chain. Some of the menus displayed on the website include: Breeders, Abattoirs, Traders, Buyers / Consumers, Halal MUI, Livestock Service Office, Indonesian Consumers Foundation